OUTCOME OF REVISION PROCEDURES FOR FAILED PRIMARY MACULAR HOLE SURGERY. Issue 7 (July 2021) - Maguire, Matthew J.; Steel, David H.; Yorston, David; Hind, Jennifer; El-Faouri, Muhannd; Jalil, Assad; Tyagi, Pallavi; Wickham, Louisa; Laidlaw, Alistair H.
Abstract : Purpose: To analyze the outcomes of revision surgery for idiopathic full-thickness macular holes that have failed to close after primary surgery, and also to assess factors predicting success and to review the relative effect of adjunctive surgical techniques. Methods: A multicenter retrospective study. Anatomical closure rates and visual acuity change between pre and postrevision surgery were assessed. Hole size, age, symptom duration, surgical interval, and reduced hole size were analyzed as predictive factors for success. Effectiveness of adjunctive surgical techniques was reviewed. Results: Seventy-seven eyes were included in the study. Anatomical closure was achieved in 71% (55/77) cases. There was a median gain of 11 Early Treatment of Diabetic Retinopathy Score letters in all holes and 14 letters in closed holes. Full-thickness macular holes that increased in size by more than 10% following primary surgery had a closure rate of 50% compared with 80% in holes that reduced by 10% or stayed the same ( P = 0.015). Increasing hole size is associated with a modest reduction in odds of closure (odds ratio = 0.99; P = 0.04). Surgical interval <2 months is not associated with better outcomes compared with >2 months ( P = 0.14). Conclusion: Revision surgery for full-thickness macular holes that have failed to close after primary surgery is associated with high closure rates and significant visual gains. Abstract : Revision surgery for idiopathic full-thickness macular holes that have failed to close with primary surgery is effective at achieving anatomical closure and improving visual acuity.